Mouse models of thyroid cancer: Bridging pathogenesis and novel therapeutics. (28th January 2020) - Jin, Yuchen; Liu, Min; Sa, Ri; Fu, Hao; Cheng, Lin; Chen, Libo
Abstract: Due to a global increase in the incidence of thyroid cancer, numerous novel mouse models were established to reveal thyroid cancer pathogenesis and test promising therapeutic strategies, necessitating a comprehensive review of translational medicine that covers (i) the role of mouse models in the research of thyroid cancer pathogenesis, and (ii) preclinical testing of potential anti-thyroid cancer therapeutics. The present review article aims to: (i) describe the current approaches for mouse modeling of thyroid cancer, (ii) provide insight into the biology and genetics of thyroid cancers, and (iii) offer guidance on the use of mouse models for testing potential therapeutics in preclinical settings. Based on research with mouse models of thyroid cancer pathogenesis involving the RTK, RAS/RAF/MEK/ERK, PI3K/AKT/mTOR, SRC, and JAK-STAT signaling pathways, inhibitors of VEGFR, MEK, mTOR, SRC, and STAT3 have been developed as anti-thyroid cancer drugs for "bench-to-bedside" translation. In the future, mouse models of thyroid cancer will be designed to be ''humanized" and "patient-like, " offering opportunities to: (i) investigate the pathogenesis of thyroid cancer through target screening based on the CRISPR/Cas system, (ii) test drugs based on new mouse models, and (iii) explore the underlying mechanisms based on multi-omics. Highlights: The cell line/patient-derived and genetically engineered mouse models of thyroid cancer are increasing and ever-evolving. Pathway activation of MAPK, PI3K, SRC, and JAK-STAT was proved to play roles on thyroid cancer progression in mouse models. Inhibitors of VEGFR, MEK, mTOR, SRC, and STAT3 were tested in thyroid cancer mouse models, showing translational potential. CRISPR, humanization, and multi-omics are techniques of promise for wide application in thyroid cancer research in vivo .